2012
DOI: 10.1149/2.062203jes
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of GaAs Photovoltaics Due to Sol-Gel Derived Anti-Reflective AZO Films

Abstract: Aluminum (Al)-doped ZnO (AZO) thin films are prepared via the sol-gel method and utilized as an anti-reflective coating (ARC) to enhance the light gathering capability and short-circuit current density (J sc ) of GaAs solar cells. The AZO films are prepared chemically by spin coating the sol with an aqueous solution of zinc acetate dihydrate and aluminum nitrate. The current-voltage measurements of the solar cells confirm that the AZO film increases short-circuit current. 4 atom% Al-doped ZnO film exhibits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Experimental Tauc plots were digitized from 73 plots collected from 63 published works, and the extracted slope values were collected into a histogram binned by order of magnitude. Additionally, the collected slopes, NEAR values, and reported and fitted E g values are shown in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental Tauc plots were digitized from 73 plots collected from 63 published works, and the extracted slope values were collected into a histogram binned by order of magnitude. Additionally, the collected slopes, NEAR values, and reported and fitted E g values are shown in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ZnO is ideal for this study because as it is a closely stoichiometric material easily synthesized through a number of methods, indicating that the samples considered in published work should be relatively uniform in character, allowing us to address the Tauc method rather than bias arising from sample variability. Zinc oxide thin films can be fabricated using methods such as sol‐gel, chemical vapor deposition, hydrothermal, or solvothermal growth, magnetron sputtering, and pulsed laser deposition (PLD) . It is stable in a hexagonal wurtzite structure with lattice parameters of c = 5.205 Å, a = 3.249 Å .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous deposition methods are available for zinc oxide thin films including sol-gel [24][25][26][27][28][29], chemical vapor deposition [9,18,30,31], hydrothermal [32,33] or solvothermal growth [34], magnetron sputtering [35][36][37][38], and pulsed laser deposition (PLD) [39][40][41][42]. It is stable in a hexagonal wurtzite structure with lattice parameters of (c ¼ 5.205 Å, a ¼ 3.249 Å) [43].…”
mentioning
confidence: 99%
“…ZnO is usually a preferred material, mainly because of its low cost, high-quality films, less toxicity, and its implementation is more straightforward [310][311][312][313]. Also, a single layer ZnO coating produces an equivalent enhancement of performance or even a cut above the multiple-layer coatings for GaAs and Silicon solar cells [314,315]. Makableh et al reported an improvement in the performance of the GaAs cell by employing a Zinc oxide ARC deposited by the sol-gel technique.…”
Section: Gallium Arsenide Based Solar Cells (Gaas)mentioning
confidence: 99%